YESUS SANG ANAKMenggali Hubungan Kekal Dengan Allah Bapa Dan Implikasi Teologisnya - Abraham Mayor; Delsiana Palayukan; Dwiwanti Udeng Tangibali (Adisam Publisher, 2025)
This study aims to delve deeper into the theological implications of the eternal relationship between Jesus the Son and God the Father, especially in the context of 1 John. The research was conducted by analyzing biblical texts relevant to the topic. The results show that the eternal relationship between Jesus and God the Father is affirmed through the identification of Jesus as the Word of Life who has an intrinsic relationship with God the Father from eternity. Theological implications include showing a harmonious model of God-man ideal relations, Jesus as a bridge of reconciliation between man and God, and as a basis for understanding the eternal life of believers. This understanding is also relevant to communities of believers because it shapes their view of a relationship with God, strengthens the belief in salvation, and as a basis for hope for God's help.